FREQUENCY AND IMPACT OF HYPERTENSIVE DISORDERS OF PREGNANCY - Perveen, Shakira (Journal of Ayub Medical College Abbottabad, 2014)
Background: Hypertensive disorders are one of a major cause of maternal mortality and morbidity especially in developing countries. This cross sectional descriptive study was carried out to determine frequency of hypertensive disorders of pregnancy and its impact on maternal and perinatal outcome. Methods: Records of 150 pregnant hypertensive ladies presenting at gynaecology Unit-1 of Civil Hospital Karachi from January to December 2010 was reviewed for demographic profile, mode of delivery, maternal and perinatal outcome. Statistical analysis was performed by SPSS-15. Results: Total deliveries during study period were 2702. Out of 2702 deliveries 150 (5.5%) mothers were hypertensive. Out of 150 hypertensive cases 30% were cases of gestational hypertension, 58% were cases of toxaemia of pregnancy and 12% were cases of chronic hypertension. Maternal age, gravida, parity was lowest in toxaemia of pregnancy group. Commonest maternal complication was eclampsia (32%). There were 6 (4%) maternal deaths. Caesarean section was mode of delivery in 54% cases. Conclusion: Hypertensive disorders of pregnancy are an important cause of maternal and perinatal mortality and morbidity. Keywords: Preeclampsia, eclampsia, maternal mortality, perinatal mortality rate.